Hearing the voice of remote Aboriginal and Torres Strait Islander training stakeholders using research methodologies and theoretical frames of reference. Issue 2 (4th March 2017) - Guenther, John; Osborne, Sam; Arnott, Allan; McRae-Williams, Eva
Abstract: Researchers in remote Aboriginal and Torres Strait Islander contexts within Australia are frequently faced with the challenges of working in an intercultural space where channels of communication are garbled with interference created by the complexities of misunderstood worldviews, languages, values and expectations. A concern of many researchers in these contexts is to ensure that the voices of research participants in remote communities are not only accurately represented, but are allowed to transcend the noise of dominant paradigms, policies and practices. This article brings together the experiences of four non-indigenous researchers in the space of remote vocational education and training. The authors present two vignettes from research in the context of health, employment and education. These vignettes highlight some of the conundrums for researchers as they attempt to harmonize the aims of research with the expectations of organizations involved. The purpose of the article is to explore the utility of Critical Race Theory (CRT), Indigenist methodologies, culturally responsive methodologies and those positioned at the 'cultural interface' (Nakata 2007). In so doing this article makes some assessments about the fit of CRT methodologies for such contexts.